Analysis of Net Profit Achievement Using the Cost Plus Pricing Approach in the Tahu Tempe Sumali Micro Business Unit in Tolitoli Regency - Usman, Usman; Nurfitriana, Nurfitriana; Ijma, Ijma; Wulandari, Putri (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to analyze the achievement of net profit in the Tofu Tempe Sumali Micro Business Unit in Tolitoli Regency using a cost plus pricing approach. This approach was chosen to assess the effectiveness of determining the selling price of products based on the total cost of production plus the expected profit margin. The methodology used is a qualitative, descriptive and quantitative approach with case studies. Data was obtained through direct observation, interviews, and financial statement documentation. The results of the study show that the application  of cost plus pricing is able to provide a more accurate picture of the decent selling price and increase the achievement of net profit. It was found that the main cost component consists of soybean raw materials, labor costs, energy costs (electricity and water), and distribution costs. Indirect costs such as tool depreciation and maintenance are also recorded manually. Based on the existing cost structure and the overall budget value, the net profit achievement based on the cost plus pricing method is Rp.185,502,600. Net Profit Comparison, the calculation of the Cost plus Pricing approach results in an effective price of Rp.7,364/Package in the Tolitoli local market environment which results in a profit of Rp. 185,502,000 while the calculation of net profit by the company's own method is Rp.151,593,000.This study recommends simple cost accounting training to micro business actors to improve financial literacy and business competitiveness.